2021
DOI: 10.3390/diagnostics11060940
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Folate as Predictors of MMSE in Alzheimer’s Disease: A Machine Learning Analysis

Abstract: Vitamin D (VD) and micronutrients, including folic acid, are able to modulate both the innate and the adaptive immune responses. Low VD and folic acid levels appear to promote cognitive decline as in Alzheimer’s disease (AD). A machine learning approach was applied to analyze the impact of various compounds, drawn from the blood of AD patients, including VD and folic acid levels, on the Mini-Mental State Exam (MMSE) in a cohort of 108 patients with AD. The first analysis was aimed at predicting the MMSE at rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Hypovitaminosis is implicated in the pathogenesis of various disorders [ 334 , 335 ], and there is increasing evidence that vitamins also play a key role in neurodegenerative diseases, leading to hypotheses concerning their use as disease biomarkers [ 336 , 337 ]. Regarding AD, although preliminary data are certainly encouraging, and the role of vitamins as biomarkers for AD has been widely investigated in literature ( Table 3 ) [ 188 , 297 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 , 350 , 351 ], some limitations in terms of consistency, reproducibility, and specificity remain to be solved, and further research is needed before hypothesizing a clinical application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypovitaminosis is implicated in the pathogenesis of various disorders [ 334 , 335 ], and there is increasing evidence that vitamins also play a key role in neurodegenerative diseases, leading to hypotheses concerning their use as disease biomarkers [ 336 , 337 ]. Regarding AD, although preliminary data are certainly encouraging, and the role of vitamins as biomarkers for AD has been widely investigated in literature ( Table 3 ) [ 188 , 297 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 , 350 , 351 ], some limitations in terms of consistency, reproducibility, and specificity remain to be solved, and further research is needed before hypothesizing a clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a small study conducted on 48 patients followed up after 7–9 years showed a diminished amount of folate in the blood of MCI patients converting to AD [ 297 ]. When using machine learning approaches, the concomitant findings of reduced blood levels of folic acid and vitamin D were confirmed to be predictive of worse MMSE scores (that is, a more pronounced cognitive impairment), thus suggesting a possible link with disease severity [ 343 ]. Moreover, diminished levels of circulating vitamin B 12 in patients with AD were reported in another recent case-control study [ 344 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D enhances the immune function and may delay aging; thus, it may play a role in the treatment of AD[ 94 ].…”
Section: Ad and Micronutrientsmentioning
confidence: 99%
“…ML algorithms can use a large amount of data and extract meaningful results from them. As such, ML can be used in several applications: for classifying patients, predicting future outcomes and even individualize patients' treatment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%